Regard rapproché, regard éloigné dans la critique d’art, de Diderot à Huysmans - Michel Delon (Modern Languages Open)
Throughout his Salons, Diderot meditated on the distance from which one should view a painting. Chardin’s paintings fascinated him, transforming with every step back taken by the viewer. Form is born from matter; meaning derives from the thickness of the colour. Whereas Pascal and classical thought proposed a correct distance in both morality and art – such a distance being difficult to determine yet ideally fixed – the eighteenth-century philosophe prized the viewer’s mobility and the relativity of perspective. Our moral judgement, as well as our aesthetic judgement, depends on the distance from which we perceive that which touches us. The short-sighted person who draws near to the object and the long-sighted person who steps away cannot share the same perception. The Lettre sur les aveugles is thus extended by a reflection on the pathologies of the gaze. The question of distance pertains to the scenography of exhibitions and the layout of displays, in private and public spaces. It contrasts painting (an art of adding colour that requires the viewer to step back) to sculpture (an art of subtracting matter that requires the viewer to step forward). It sets up two types of artists: one attentive to detail, the other rather more concerned by the ensemble. And it perhaps allows one to judge the greatest creators as those capable of being viewed from both near and far. Diderot’s art criticism was increasingly known through the nineteenth century, nourishing the period’s thought. Yet, in the wake of his innovations, this fine balance between meticulous observation and a piece perceived solely from a distance became the happy medium so dear to the postrevolutionary bourgeoisie. From Balzac’s Chef-d’œuvre d’un inconnu to Baudelaire’s Salons, from the Goncourt brothers to Huysmans, short- and long-sightedness, line and colour, the detail and the whole maintain the dynamic of the aesthetic effect and stoke the controversies of art criticism. Diderot the materialist and Huysmans the spiritualist meet to celebrate the miracle of art, which brings forth beauty from mere material pigments. Each incites the viewer to restlessness and curiosity in front of the artwork. Returning to the eighteenth century, Watteau’s Enseigne de Gersaint may be interpreted as a parable about this dual modality of the gaze and, turning finally to the twenty-first century, Pierre Soulages’s work may be seen as an invitation to shift back and forth before his monumental canvases so as to catch the movement of his art. Résumé De Salon en Salon, Diderot s’est interrogé sur la distance d’où regarder une peinture. Chardin l’a fasciné, dont les peintures se transforment au fur et à mesure qu’on s’éloigne. La forme y naît de la matière, le sens se dégage de l’épaisseur de la couleur. Alors que Pascal et la pensée classique postulaient une juste distance en morale comme en art, distance difficile à déterminer mais idéalement fixe, le philosophe du dix-huitième siècle revendique la relativité du point de vue et la mobilité de l’observateur. Notre jugement moral, aussi bien que le jugement esthétique, dépendrait de la distance d’où nous percevons ce qui nous touche. Le myope qui doit se rapprocher et le presbyte qui doit s’éloigner ne peuvent avoir la même perception. La Lettre sur les aveugles est ainsi prolongée par une réflexion sur les pathologies du regard. La question de la distance engage la scénographie des expositions et le dispositif des accrochages, dans des espaces privés ou publics. Elle oppose la peinture, art de l’ajout de touches colorées, qui nécessite le recul, à la sculpture, art de la soustraction de matière, qui appelle un rapprochement. Elle détermine deux types d’artistes, attentif au détail ou bien plus soucieux de l’ensemble. Elle permet peut-être de juger les plus grands créateurs, capables d’être regardés de près aussi bien que de loin. La critique d’art de Diderot a été découverte progressivement au cours du dix-neuvième siècle et a nourri la réflexion de l’époque. Mais loin de ses audaces, un équilibre entre l’observation méticuleuse et une tournure globale, perçue seulement de loin, devient un juste milieu cher à la bourgeoisie post-révolutionnaire. Du Chef d’œuvre inconnu de Balzac aux Salons de Baudelaire, des frères Goncourt à Huysmans, la myopie et la presbytie, le dessin et la couleur, le détail et l’ensemble assurent la dynamique de l’effet esthétique et alimentent les controverses de la critique d’art. Diderot le matérialiste et Huysmans le spiritualiste se rencontrent pour célébrer le miracle de l’art, capable de faire surgir la beauté de la seule matérialité des pigments. Ils encouragent, l’un et l’autre, le spectateur à un mouvement inquiet et curieux devant l’œuvre d’art. En revenant au dix-huitième siècle, on peut interpréter L’Enseigne de Gersaint de Watteau comme une parabole sur cette double modalité du regard et, en venant jusqu’au vingt et unième siècle, la création de Pierre Soulages devient une invitation à se déplacer devant ses toiles monumentales pour y surprendre le mouvement de la création.